Pelaksanaan Keterbukaan Informasi Publik di Universitas Jambi: Suatu Telaah Normatif - Akbar Kurnia Putra; Sulhi Muhammad Daud Abdul Kadir (Universitas Negeri Medan, 2020)
Openness of public information is one of the pillars of freedom of expression and the pillars of democracy, transparency and good governance. To encourage public participation, Law Number 14 of 2008 concerning Openness of Public Information was born. The provision regulates social norms to obtain data access and guarantees that each individual fulfills his basic rights. This research is focused on the implications of these regulations at the University of Jambi. As a public body, the University of Jambi is required to apply all the provisions that have been set. Aside from being a controlling system, this policy must be addressed as part of bureaucratic reform, especially regarding good governance so that the fundamental changes that occur are directly proportional to the area of change desired. The research methodology uses the normative type of jurisprudence, namely by examining the legal literature through the study of documents with the nature of analytic description so as to produce systematic factual basis.